Investigasi Kualitas Tanah pada Pembangunan Kelapa Sawit PT. Tunas Harapan Baru: Soil Quality Investigation for Palm Oil Plantation Development at PT. Tunas Harapan Baru - Diharyo, Diharyo; Santoso, Achmad Imam; Lesmana, Rudy Yoga (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
This study aims to evaluate the soil conditions of the land used for palm oil plantation development at PT. Tunas Harapan Baru. The evaluation was conducted by analyzing the physical and chemical properties of the soil, including texture, pH, organic matter content, and key nutrients. Data were obtained from laboratory tests on several soil samples from the location. The results showed that the soil conditions are suitable for palm oil plantation development, although some parameters require attention in sustainable land management. This article also discusses the environmental impact of land use for plantations on local soil conditions and provides recommendations for improving soil quality.